Tax incentives, environmental regulation and firms’ emission reduction strategies: Evidence from China - Qi, Yu; Zhang, Jianshun; Chen, Jianwei (Journal of environmental economics and management, 2023)
Policy interaction is an important way to deal with increasingly complex environmental problems. This paper examines the investment-related tax cuts and the policy interaction with environmental regulation on firms' emission reduction strategies. Taking China's value-added tax (VAT) reform as a quasi-natural experiment and considering the interaction with the emission reduction target policy, our difference-in-differences estimation shows that: the average effect of the VAT reform reduces firms' sulfur dioxide (SO2) emission intensity by 16.6%, due to the adoption of emissions reduction strategies in the production processes; the interaction effect between the VAT reform and environmental regulation incentivizes firms to additionally reduce SO2 emission intensity, due to the adoption of both production processes and end-of-pipe reduction strategies. Our findings are more evident for firms with tight financial constraints. Overall, this paper reveals the micro-mechanisms of how the tax policies incentivize firms to choose emission reduction strategies and highlights the importance of the interaction effects between environmental and non-environmental policies, thus providing implications for the policy mix of environmental regulation and tax-cut incentives to promote pollution reduction and improve business performance.